Risperidone in the treatment of mixed state bipolar patients: Results from a 24‐week, multicenter, open‐label study in Korea - Woo, Young Sup; Bahk, Won‐Myong; Jon, Duk‐In; Chung, Sang‐Keun; Lee, Sang‐Yeol; Ahn, Yong Min; Pae, Chi‐Un; Cho, Hyun‐Sang; Kim, Jeong‐Gee; Hwang, Tae‐Yeon; Lee, Hong‐Seok; Min, Kyung Joon; et al. (Psychiatry and clinical neurosciences, 2010)
Aims:  The goal of the present study was to evaluate the efficacy of risperidone combined with mood stabilizers for treating bipolar mixed state. Methods:  The present study was a 24‐week, open‐label, combination, prospective investigation of the efficacy of risperidone in combination with mood stabilizers. Risperidone (1–6 mg/day) was given in combination with mood stabilizers in flexible doses according to clinical response and tolerability for 114 patients in mixed or manic episode. Results:  Forty‐four patients met our criteria for mixed state bipolar disorder and 70 met the criteria for pure mania. Mean age for the subjects was 39.0 ± 11.0 years and 55.3% were female. The combination of risperidone with mood stabilizers significantly improved the scores on the Young Mania Rating Scale (YMRS), 17‐item Hamilton Rating Scale for Depression (HAMD), 18‐item Brief Psychiatric Rating Scale (BPRS), Global Assessment Scale (GAS), and Clinical Global Impression Scale for use in bipolar illness Severity (CGI‐BP) at 24 weeks (P < 0.0001). Analysis of the YMRS, BPRS, GAS, and CGI‐BP scores showed significant improvement in both the manic and mixed groups. The rate of response in YMRS scores was 84.2% (n = 96) and the rate of YMRS remission was 77.2% (n = 88) at week 24 in the total population. Seventy‐four patients met both YMRS ≤ 12 and HAMD ≤ 7 at week 24 (64.9%). Risperidone was well tolerated, and adverse events were mostly mild. Conclusion:  The combination of risperidone with mood stabilizers was an effective and safe treatment for manic symptoms and coexisting depressive symptoms of bipolar disorder.